Factors Associated With Online Learning Self-Efficacy Among Students With Disabilities In Higher Education. Issue 4 (2nd October 2021) - Lee, Othelia EunKyoung; Kim, Stella Y.; Gezer, Tuba
ABSTRACT: This study examined how the prevalence of online learning increases educational outcomes and access for students with disabilities, exploring the factors associated with these learners' self-efficacy in virtual environment. College students with disabilities (n = 278) were surveyed about their experience with online courses, overall technology competence, and preferred instructional modalities. Online learning self-efficacy (OLSE) was used as the outcome. Factors associated with OLSE were technological competence and delivery preferences. Students with medical disabilities, in comparison to their peers with a psychological and/or learning disability, reported a higher level of OLSE in the virtual environment. These factors collectively accounted for 33.7% of the variance in OLSE ( R 2 = .36, F = 19.631, p < .001). Improving the accessibility of online learning for students with disabilities will promote best practices in online learning for all students. Accessibility mind-sets have been increasingly called for as higher education institutions are offering online courses.